UMPSA announces winner of Writing Contest for 21st Anniversary - Nor Salwana, Mohammad Idris (UMPSA, 2023)
PEKAN, 18 December 2023 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) announced three winners and two consolation prizes for the 2023 Article/Scientific/Commentary Writing Competition organised by the Centre for Corporate Communications (PKK) recently, in conjunction with 21 Years of UMPSA.